Implikasi Paralelisme Janus dalam Filipi 3:9 Bagi Iman Percaya Masa Kini - Candra Gunawan Marisi (Sekolah Tinggi Teologi Real Batam, 2022)
Paul is a great writer. As a Pharisee is undoubtedly his skill as an interpreter and writer with the semistic style seen in parts of his writings. The basic point for understanding the epistles, however, is that in the Jewish and Pharisee backgrounds it remained an integral part of Paul. His identity as a Jew and his concern for his nation's heritage provide one side of dialogue that continues throughout the letter, an arch that runs back and forth across patterns. Likewise, in Paul's writings in Philippians 3:9, there is a central point of Paul's belief in God's justification. This research was conducted using a qualitative method with a semantic analysis approach, namely with the literary style of Janus parallelism and the polysemy parallelism approach to texts. There is a literary style of Janus's parallelism in Paul's writing style in Philippians 3:9. Through this method of parallelism Janus can look deeper into the meaning written by Paul of